Ostomy and Continent Diversion Patient Bill of Rights: Research Validation of Standards of Care. Issue 3 (May 2022) - Burgess-Stocks, Joanna; Gleba, Jeanine; Lawrence, Kathleen; Mueller, Susan
Abstract : An estimated 725, 000 to 1 million people are living with an ostomy or continent diversion in the United States, and approximately 100, 000 ostomy surgeries are performed each year in the United States. As a result of ostomy surgery, bodily waste is rerouted from its usual path because of malfunctioning parts of the urinary or digestive system. An ostomy can be temporary or permanent. The ostomy community is an underserved population of patients. United Ostomy Associations of America, Inc (UOAA), is a nonprofit organization dedicated to promoting quality of life for people with ostomies and continent diversions through information, support, advocacy, and collaboration. Over the years, UOAA has received hundreds of stories from people who have received inadequate care. In the United States, patients receiving medical care have certain health rights. For ostomy and continent diversion patients, these rights are known as the "You Matter! Know What to Expect and Know Your Rights—Ostomy and Continent Diversion Patient Bill of Rights" (PBOR). These rights define and provide a guide to patients and health care professionals as to what the best practices are when receiving and providing high-quality ostomy care during all phases of the surgical experience. This includes preoperative to postoperative care and throughout the life span when living with an ostomy or continent diversion. In 2020, the National Quality Forum released "The Care We Need: Driving Better Health Outcomes for People and Communities, " a National Quality Task Force report that provides a road map where every person in every community can expect to consistently and predictably receive high-quality care by 2030 (thecareweneed.org). One of the core strategic objectives this report stated is to ensure appropriate, safe, and accessible care. Actionable opportunities to drive change include accelerating adoption of leading practices. The adoption of the PBOR best practices will drive the health care quality improvement change needed for the ostomy and continent diversion population. There are concerns in the ostomy and continent diversion communities among patients and health care professionals that the standards of care outlined in the PBOR are not occurring across the United States in all health care settings. There are further concerns stated by health care professionals that the patient-centered recommendations outlined in the PBOR need to be strengthened by being supported with available published health care evidence. The work of this task force was to bring together members of UOAA's Advocacy Committee, members of the Wound, Ostomy, and Continence Nurses Society (WOCN Society) Public Policy and Advocacy Committee, and representatives from surgical organizations and industry to create a systemic change by validating through evidence the Ostomy and Continent Diversion PBOR. Through the work of the task force, each component of the PBOR has been substantiated as evidence-based. Thus, this article validates the PBOR as a guideline for high-quality standards of ostomy care. We show that when patients receive the standards of care as outlined in the PBOR, there is improved quality of care. We can now recognize that until every ostomy or continent diversion patient receives these health care rights, in all health care settings, will they truly be realized and respected as human rights in the United States and thus people living with an ostomy or continent diversion will receive "the care they need."